Classification of analog modulated communication signals using clustering techniques: A comparative study - Guldemir, Hanifi; Sengur, Abdulkadir (My University, 2005)
In this paper, a comparative study of classification of the analog modulated communication signals using clustering techniques is introduced. Four different clustering algorithms are implemented for classifying the analog signals.These clustering techniques are K-means clustering, fuzzy c-means clustering, mountain clustering and subtractive clustering. Two key features are used for characterizing the analog modulation types. Performance comparison of these clustering algorithms is made using computer simulations.
Keywords: Mühendislik; Elektrik ve Elektronik; Bilgisayar Bilimleri; Yazılım Mühendisliği